Peran Keterikatan Karyawan pada Pengaruh Gaya Kepemimpinan Terhadap Kepuasan Kerja - Alvanda, Alvanda; Bidayati, Utik (University of Merdeka Malang, 2024)
This study aims to analyze the role of leadership style on employee engagement towards job satisfaction. The research employs a quantitative method, using non-probability sampling techniques with a sample size of 53 respondents from employees of Ahmad Dahlan University Hospital. Data collection in this study was conducted using a questionnaire, and the data were processed using Path Analysis SEM PLS by evaluating the outer model and inner model. The results of this study indicate that leadership style has a positive and significant effect on employee engagement; leadership style has a positive and significant effect on job satisfaction, and employee engagement mediates the relationship between leadership style and job satisfaction. Therefore, Ahmad Dahlan University Hospital needs to pay attention to leadership style and employee engagement to achieve better levels of employee satisfaction.